The effects of increased temperature and CO2 on the Amazon fish, tambaqui (Collosoma macropomum, Cuvier, 1818) - Safi, Amtyaz; Baptista, Ramon Barros (International Journal of Biological Research, 2013)
The effect of Changed temperature and carbon dioxide (CO2) variations on LDH (Lactate de Hydrogenase), MDH (Malate de Hydrogenase) & GST (Glutathione-S-Transferase) enzymes of muscles and MDH & GST Enzymes of liver of Tambaqui fish (Collosoma macropomum,Â Cuvier, 1818) were studied in the Laboratory of Ecophysiology and Molecular Evolution (LEEM) of the National Institute for Amazonian Research (INPA). The initiative involves exposing fish to a temperature rise from 28C to 32C and a CO2Â concentration up to 10 times higher than today for 24, 48, 72 and 96 hours. The level of LDH, GST and MDH in both the tissues of Tambaqui (Muscles & Liver) showed a significant decreased at different exposure period. The level of Glucose in blood showed decreased and the values of Hb, Ht, RBC, VCM, HCM & CHCM showed increased at that exposure.